2014
DOI: 10.11646/phytotaxa.191.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Description of the pseudocryptic species Conticribra weissflogiopsis sp. nov. (Thalassiosirales, Bacillariophyta) isolated from brackish waters in Korea, based on its cingulum structure and molecular analysis

Abstract: We describe the new fultoportulate diatom species, Conticribra weissflogiopsis, isolated from brackish waters in Korea, based on morphological characters and molecular data. The new species is characterized by having areolae venation with internal (semi-) continuous cribra, a flat valve face, a single marginal rimoportula replacing a marginal fultoportula, a subcentral ring of the valve face fultoportulae, and a dextral pattern of cingulum structure. The overall valve structure of C. weissflogiopsis resembles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…This was especially evident for the two strains of C. sinica, which exhibited the largest inter-specific genetic distance with the other Conticribra species (i.e., 0.03 -0.09 p-distances). These sequence comparisons are consistent with those from Park et al (Park et al 2014), and the topology of clustering patterns in our phylogenetic analysis.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This was especially evident for the two strains of C. sinica, which exhibited the largest inter-specific genetic distance with the other Conticribra species (i.e., 0.03 -0.09 p-distances). These sequence comparisons are consistent with those from Park et al (Park et al 2014), and the topology of clustering patterns in our phylogenetic analysis.…”
Section: Resultssupporting
confidence: 92%
“…The presence of valve face fultoportulae is a characteristic that distinguishes living and fossil Conticribra species. C. guillardii have 0-4 valve face fultoportulae (Hasle 1978), C. weissflogii exhibits many valve face fultoportulae on the subcentral area (Fryxell & Hasle 1977), and C. weissflogiopsis exhibits 2-12 valve face fultoportulae on the subcentral area (Park & Lee 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The genomic DNA was extracted from cell pellets by using a DNeasy® Plant Mini Kit (Qiagen, Hilden, Germany). Nuclear rDNA fragments [i.e., nearly full-length small subunit ribosomal DNA ( SSU rDNA) gene and the D1–D3 region of the large subunit ribosomal DNA ( LSU rDNA)] and plastid-encoding genes ( psb C and rbc L) were amplified and sequenced following protocols outlined in Alverson et al [ 3 ] and Park & Lee [ 20 ]. Newly generated DNA sequences are available from GenBank using accession numbers KY912618, KY912621, KY912624, and KY912625 for T .…”
Section: Methodsmentioning
confidence: 99%
“…GQ414523) were analyzed using the blast search in NCBI. The molecular data in the present paper suggested that C. weissflogii (ND-8) and other Conticribra species form a monophyletic group separated from some species of Thalassiosira, which was described as a new species from three additional areas of Korea (Park and Lee, 2014). In 18S analysis, C. weissflogii (ND-8) clustered with C. weissflogii (EF585582) ( Figure 1C ), T. oceanica (AF374479) and T. fluviatilis (AJ535170), and with a sister clade comprising C. guillardii (AF374478).…”
Section: Resultsmentioning
confidence: 60%